Is urine interleukin-8 level a reliable laboratory test for diagnosing late onset sepsis in premature infants? - Bentlin, Maria Regina [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Rugolo, Antonio; Hashimoto, Miriam [UNESP]; Lyra, João César [UNESP] (Oxford University Press, 2007)
The present study is aimed to determine serum and urine interleukin-8 (IL-8) levels in premature infants with late onset sepsis (LOS) and to evaluate if urine IL-8 is a useful test for LOS diagnosis. Fifty-six premature infants admitted to the NICU over 1 year had serum and urine IL-8 determined by ELISA. They were divided into three groups: I definite sepsis, II probable sepsis and III non-infected. Results were expressed as mean or median. Differences between groups were assessed by ANOVA, Kruskal-Wallis ANOVA and Dunns Method. Sensitivity, specificity and positive and negative predictive values were calculated and a receiver operator characteristic curve was constructed to determine serum and urine IL-8 accuracy. There were no differences between groups for birth weight, and gestational and post-natal age. Median serum and urine IL-8 levels were significantly higher in GI and GII: 929 x 906 x 625pg/ml; P=0.024, and 249 x 189 x 42pg/mgCr; P< 0.001. Optimal cut-off point was 625pg/ml for serum IL-8 with 69 sensitivity and 75pg/mgCr for urine IL-8 with 92 sensitivity. IL-8 can be determined in urine from premature infants with LOS and is an accurate and feasible diagnosis method.